Al-Qur'an Semantic Study: The Word Istiwa' Perspective Of Toshihiko Izutsu - Nur Alif, Muhamad (ARRUS Journal of Social Sciences and Humanities, 2024)
The word "istiwa'" in the Qur'an is a term that is rich in meaning and often appears in the context of mutasyabihat verses, where it contains different nuances in each use. With nine occurrences, each verse that uses this term requires a deep understanding to reveal its essence and implications. This study aims to analyse the meaning of istiwa' with the Qur'anic semantic approach developed by Toshihiko Izutsu. Qur'anic semantics, in this context, serves as a tool to reveal the worldview (weltanschauung) of the Qur'an through in-depth analysis of key vocabulary. The methods used include syntagmatic and paradigmatic analyses to explore the basic meaning and relational meaning of the term istiwa'. The research also includes a historical study of the use of this vocabulary in pre-Qur'anic, Qur'anic and post-Qur'anic contexts, in order to provide a comprehensive picture of the evolution and interpretation of this term over time. The results of this research are expected to make a significant contribution in understanding the concept of istiwa' in the Qur'an, as well as enriching the scientific discourse on Qur'anic semantics. Through this approach, it is hoped that new insights will emerge that can deepen the understanding of the attributes of God, as well as their relevance in the context of contemporary Islamic theology.